2012
DOI: 10.1063/1.4704366
|View full text |Cite
|
Sign up to set email alerts
|

Analytic model for the efficiency droop in semiconductors with asymmetric carrier-transport properties based on drift-induced reduction of injection efficiency

Abstract: An analytic model is developed for the droop in the efficiency-versus-current curve for light-emitting diodes (LEDs) made from semiconductors having strong asymmetry in carrier concentration and mobility. For pn-junction diodes made of such semiconductors, the high-injection condition is generalized to include mobilities. Under high-injection conditions, electron drift in the p-type layer causes a reduction in injection efficiency. The drift-induced leakage term is shown to have a 3rd and 4th power dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
123
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 14 publications
4
123
0
Order By: Relevance
“…where the high power term f(n) is the electron overflow term [13,14]. If taking the carrier localization into account as well, the effective volume of the active region will be introduced [15,16], and compared with the conventional ABC model, the corrected ABC model will exhibit better fitting to the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…where the high power term f(n) is the electron overflow term [13,14]. If taking the carrier localization into account as well, the effective volume of the active region will be introduced [15,16], and compared with the conventional ABC model, the corrected ABC model will exhibit better fitting to the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…To date, research on carrier leakage of InGaN/GaN LEDs are scattered in experiment and theory, 6,8,11,15 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although many theories have attempted to explain these experimental observations, including device heating, 3 delocalization of carriers, 4 Auger recombination, 5 and electron leakage, 6 there is still no consensus on their underlying physical mechanism. Electron leakage is commonly regarded as having an important contribution to the remarkable efficiency loss, especially at high injected current.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, the carrier injection efficiency has the key functions in the light emission efficiency of GaN based LEDs. Meeyard et al [8,9] reported asymmetry during carrier transport because of the much lower concentration and mobility of holes in p-GaN and p-AlGaN compared with electrons. The asymmetry in carrier transport reduces the light emission efficiency of LEDs and enlarges the efficiency droop.…”
Section: Introductionmentioning
confidence: 99%